Effect of heat treatments on the microstructure and wear behaviour of a selective laser melted maraging steel. (December 2022) - Özer, Gökhan; Khan, Hamaid Mahmood; Tarakçi, Gürkan; Yilmaz, Mustafa Safa; Yaman, Paşa; Karabeyoğlu, Sencer Süreyya; Kisasöz, Alptekin
This study applied classical and intercritical heat treatments to maraging steel (MS1) samples produced with standard additive manufacturing (AM) production parameters. The effects of heat treatment parameters on the microstructure-phase changes of the material were investigated by optical microscope (OM), scanning electron microscope (SEM), Electron Dispersion Spectroscopy (EDX), and X-ray diffraction analysis (XRD) techniques. Likewise, microhardness and dry sliding wear tests were performed to determine the relationship of heat treatment parameters (especially intercritical heat treatment) to the mechanical properties and wear of the material. The results reveal that the intercritical heat treatment is exciting for the AM/MS1 material.